2018
DOI: 10.1364/oe.26.010109
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow loss graphene-based hybrid plasmonic waveguide with deep-subwavelength confinement

Abstract: In this paper, we theoretically propose a novel graphene-based hybrid plasmonic waveguide (GHPW) consisting of a low-index rectangle waveguide between a high-index cylindrical dielectric waveguide and the substrate with coated graphene on the surface. The geometric dependence of the mode characteristics on the proposed structure is analyzed in detail, showing that the proposed GHPW has a low loss and consequently a relatively long propagation distance. For TM polarization, highly confined modes guided in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…Kuznetsov E V et al 33 demonstrated the suppression of crosstalk between two dielectric nanowaveguides by placing an auxiliary linear waveguide between loaded waveguides spaced by one wavelength. He X et al 34 proposed an ultralow loss graphene-based hybrid plasmonic waveguide with lower crosstalk, which is much better than those reported in hybrid plasmonic waveguides 31 . Moreover, there are other plasmonic waveguides based on crosstalk researches have been published [35][36][37][38][39][40][41][42][43][44] .…”
Section: Introductionmentioning
confidence: 93%
“…Kuznetsov E V et al 33 demonstrated the suppression of crosstalk between two dielectric nanowaveguides by placing an auxiliary linear waveguide between loaded waveguides spaced by one wavelength. He X et al 34 proposed an ultralow loss graphene-based hybrid plasmonic waveguide with lower crosstalk, which is much better than those reported in hybrid plasmonic waveguides 31 . Moreover, there are other plasmonic waveguides based on crosstalk researches have been published [35][36][37][38][39][40][41][42][43][44] .…”
Section: Introductionmentioning
confidence: 93%
“…A novel hybrid plasmonic waveguide [76] based on the graphene-coated V-groove and the GCNWs was also proposed. In the literature, a lot of promising graphene-based hybrid waveguides [77][78][79][80][81][82][83][84][85][86] were analyzed in THz and mid-infrared bands. Here, we mainly focus on the GCNWs and GCNW-based hybrid waveguide, thus they will not be covered here.…”
Section: Gcnw-based Hybrid Waveguidesmentioning
confidence: 99%
“…Later, Wan et al [53] proposed a dielectric-loaded graphene groove waveguide, and a typical propagation length of about 37.8 µm and mode area of about 52 µm 2 were obtained at 1.5 THz. To achieve a better modal field confinement, two graphene-based hybrid plasmonic waveguides were proposed [54,55], which could simultaneously achieve an ultra-small modal area and a propagation length of about several hundreds of micrometers at 3 THz. Despite recent progress in graphene-based waveguides, we note that the current reports mainly focus on the near-and mid-infrared band, and graphene-based THz waveguides are studied less, relatively speaking.…”
Section: Introductionmentioning
confidence: 99%